Investigation On The Sound Absorption Properties Of Gigantochloa Ligulata Bamboo - Mayadi, Farah Hanim M Nor (Universiti Sains Malaysia, 2022)
The use of sound absorbent materials may minimise reverberation time, or the time it takes for sound to travel across a space. The use of natural resources to reduce carbon emissions during the synthesis of new materials is becoming increasingly popular including the use of natural resources as a sound absorbent. In this study, a natural material based on bamboo fibre, Gigantochloa ligulata was examined and characterized. The goal of this research is to find out how well pure bamboo fibre and resin-treated bamboo fibre can absorb sound. The sample are produced by using hydraulic press machine and the weight for each sample is 5g. The testing involved three different sizes of bamboo fibre which are 850m, 2mm, and 5mm. A total of 3 sample were produced for each size of bamboo fibre. The sound absorption coefficient (SAC) of bamboo fibre is measured using impedance tubes. The measurement was taken at three different air gap distance. It is observed that the SAC value at different air gap for each sample produced only little to no difference. However, the results shows that the highest SAC value is observed at the smallest air gap which is 10mm. For different sizes of bamboo fibre, similar pattern emerges for samples containing epoxy resin as the binder, with the largest fibre size having the highest SAC when compared to a smaller fibre size. The results shows that most of the highest peak of the sound absorption coefficient lies at the high frequency zone between 3000 to 4500 Hz with range of SAC between 0.5-0.7. These results implies that bamboo fibre looks to be a viable solution for sound absorption applications.